Roflumilast Suppresses Adipogenic Differentiation via AMPK Mediated Pathway - Xu, Wan; Zhang, Jingjing; Xiao, Jing (Frontiers in Endocrinology, 2021)
Obesity and related disorders have increasingly become global health problems over the years. In recent years, obesity has been recognized as the most important risk factor for a variety of diseases including cardiovascular diseases, type 2 diabetes, steatohepatitis, and cancer. The medical anti-obesity treatment is to intervene in the metabolic process of adipocytes by suppressing adipogenesis and promoting lipolysis. The Phosphodiesterase-4 (PDE4) pathway is involved in fat mass control and metabolic regulation. The present study aimed to investigate the effects of Roflumilast, a selective PDE4 inhibitor, on the differentiation of 3T3-L1 cells and the high fat diet-induced obesity in mice. We showed that treatment with Roflumilast inhibited lipid accumulation and triglycerides storage in mature 3T3-L1 cells, suggesting that Roflumilast suppressed adipogenesis. Mechanistically, we found that Roflumilast decreased the differentiation-induced expression of the adipogenesis genes including SREBP1C, FABP4, and Glut4, as well as their regulators including PPAR-γ and C/EBPα. Moreover, we proved that the effect of Roflumilast was dependent on the activation of the metabolic regulator AMPKα. The treatment with Roflumilast remarkably decreased the animals’ body weight, visceral adipose tissue weight, and adipocyte size in high fat diet-induced obese mice. In conclusion, our study revealed that Roflumilast suppressed adipogenesis and promoted lipolysis in cell culture and mice models via AMPK-mediated inhibition of PPAR-γ and C/EBPα. These findings imply roflumilast could have therapeutic potential in obesity-related diseases.